Increased antibodies against unfolded viral antigens in the elderly after influenza vaccination - Gulati, Upma (Blackwell Publishing Ltd, 2007)
Objective  Our studies aimed to measure the quality of antibody response to influenza vaccines in the elderly. The frequency of significant rise in hemagglutination inhibition (HAI) titer in the elderly is low and although annual vaccination reduces morbidity and mortality, better correlates of vaccine efficacy in the elderly are needed. Methods  We measured the amount and avidity of serum antibodies against native H3N2 influenza glycoproteins or denatured virus (unfoldons) in pre‐ and post‐vaccinated sera of 36 elderly subjects. Results  Eighty percent of subjects had high pre‐immunization antibody levels and only 13% showed ≥2fold increase after vaccination, but 33% showed ≥2fold increase in avidity. With increasing dosage there was a significant increase in avidity against unfoldons with 50% of subjects showing ≥2fold increase at the highest dose. Elderly subjects given subunit vaccine showed higher reactivity with unfoldons (78% of native) than younger subjects studied earlier who were given inactivated whole virus vaccine (19% of native). Conclusion  The clear inverse relationship between pre‐immunization antibody levels and antibody increase after vaccination implies that a major reason for the low frequency of antibody responses in elderly subjects is simply because they have high pre‐immunization antibody levels. Only low reactivity was observed with earlier viruses. The increased proportion and avidity of antibodies against unfoldons is of concern, as these are not protective, and vaccine developers need to be aware of the role of age or vaccine formulation in inducing anti‐unfoldon antibodies.